OPTIMALISASI PENERAPAN PENDIDIKAN KARAKTER PADA “KURIKULUM 2013” MENGGUNAKAN STRATEGI 3M DI SEKOLAH DASAR - Asyiah, Nur; Sunanto, Liyana (Universitas Pendidikan Indonesia, 2014)
The purpose of this study is to obtain the learning device (syllabus, lesson plans, and student worksheet) integrated character education using 3M strategy (Knowing Moral, Moral Feeling, and Moral Action) on the curriculum in 2013, and look at the effectiveness of the learning device for shaping the character of the participants learners. The study design used was a quasi-experimental control grouph pre test-post test. This research was conducted in SDN 3 Klangenan and SDN 1 Sumber to fourth grade students. The effectiveness of the learning device is made to be seen from the results of student learning, character assessment, student response to learning. Based on these data we can conclude the application of learning curriculum 3M 2013 using effective strategies to improve students' character.Keywords: character education, curriculum 2013, 3M strategy.